Application and evaluation of the hybrid “Problem-Based Learning” model based on “Rain Classroom” in experimental courses of medical molecular biology - Qu, Meng; Hou, Qinlong; Yu, Chunyan; Li, Xushen; Xia, Jichen; Dong, Zhiheng (Frontiers in Medicine, 2024)
Background With the advancement of society, the cultivation of medical professionals equipped with solid theoretical knowledge, a strong sense of innovation, and critical thinking has become a crucial goal in the reform of medical higher education. Over recent years, the hybrid Problem-Based Learning (hPBL) model, a blend of Problem-Based Learning (PBL) and Lecture-Based Learning (LBL), has emerged as a novel approach in the medical education reform landscape of China. The application and efficacy of the hPBL model in medical experimental courses have piqued the interest of medical educators. The aim of this study was to appraise the application and effectiveness of the hPBL model in the experimental course of Medical Molecular Biology at Beihua University. Methods Utilizing the “Rain Classroom” platform, students from the Preventive Medicine and Medical Imaging programs were allocated to either the hPBL or LBL method for their Medical Molecular Biology experimental courses. The hPBL model’s impact on students’ performance was evaluated across four domains: experimental theory, experimental operation, experimental report, and practical application. Questionnaires were employed to gauge students’ experiences and perceptions. Results The results indicated that the final assessment scores of the hPBL group were significantly superior to those of the LBL group. Moreover, the hPBL model effectively amplified students’ self-learning capability, practical application skills, and communication competencies. Students expressed a high degree of satisfaction with this blended learning model. Conclusion The hPBL model, which amalgamates PBL and LBL, has demonstrated its effectiveness in medical education. Its implementation in the experimental course of Medical Molecular Biology at Beihua University yielded positive outcomes, enhancing students’ performance and satisfaction levels. Consequently, it is recommended that the hPBL model be further promulgated in other medical experimental courses.